Litsea ghatica Saldanha-a New Distributional Record to Kerala State - Subramanian, K. N.; Gurudev Singh, B.; Venkatasubramanian, N.; Sasidharan, K. R. (Indian Forester, 1989)
Litsea ghatica Saldanha hitherto recorded from the Western Ghat area of Karnataka is now traced from further south in Wynad Forest Division, Kerala State. A brief description of the taxon for easy iodentification aod the salient differences of the same with Litsea deccanensis Gamble, a closely allied species, are given. The need for the conservation and protection of the species is highlighted.